Anna Kang’s Picture Books: Inculcating Young Minds with Social-Emotional Literacy - Tisnawijaya, Christy; Kurniati, Geni (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
Picture books, as one of the genres in children’s literature, have been produced and reproduced with a wide range of themes: relationships (family and friendship), emotions (accepting and compassion), behaviors (generosity, persistence), life transition (growing up, grief) and more. Picture books promote social-emotional literacy – how to behave and interact with humans and the environment – and display multimodal narrative techniques – verbal and visual texts. Research has proved that using picture books in formal classes for young learners helps in vocabulary acquisition. Moreover, the enchanting stories of picture books elevate the moral of understanding diversities. This study used library research to discuss how picture books promote literacy and how narrative styles build social emotional learning. Several sample picture books by Anna Kang were examined in terms of aspects of language play, such as the use of verbal and visual texts and the social issues they represented. The discussion exposes picture books as a medium that encourages social-emotional literacy.